“Is There Room for Both Loves?”: The Experience of Couplehood Among Women Living With a Widower With Young Children - Peichich-Aizen, Talia; Segal-Engelchin, Dorit (Frontiers in Psychology, 2022)
Very few studies to date have explored the couplehood relationship in blended families with young children created after widowhood. The current study sought to add to our knowledge of this issue by examining the couplehood experience of women who started a family with a widower with young children, with no children of their own. Semi-structured interviews were conducted with 30 Israeli women aged 32-78. The findings indicate that many participants feel that the deceased wife continues to be present in their partner’s life and that she is an integral part of their couplehood relationship. The participants described two subsystems existing alongside the couple subsystem with their partner: the partner’s spousal subsystem with his first wife; and a triadic subsystem consisting of the woman, her partner, and his deceased wife. The perceived presence of the first wife raised poignant questions concerning the place of the two women in the partner’s life. Participants’ narratives revealed the dissonance between understanding and acknowledging their partner’s continuing bond with and affection for his deceased wife on the one hand, and recognition of his love for them on the other. The findings shed light on the complexity inherent in a couple relationship with a widower, and may assist professionals who provide support to blended families in understanding the unique challenges faced by these women. This would enable them to tailor their counseling and the therapeutic process to the particular needs of these women.